An Implementation of the Eigenvalue Localization Algorithm for Threshold Graphs in Python - Eckhardt, Andressa de Oliveira (2025)
A threshold graph of order n may be characterized by a binary sequence (b1, b2, … , bn). We shall present the particulars of the algorithm known as Diagonalize, which provides the location of the eigenvalues of the adjacency matrix of a threshold graph, relying solely on its geometry, without the need for direct manipulations with the matrix itself. We shall observe that the binary characterization is a facilitative tool for a linear implementation of this algorithm in Python.